Kaji Eksperimental Retrofit R-134a Menjadi R-600a Terhadap Kinerja Sistem Cold Handling Unit - Listya Utari; Fitto Ramadhan; Muhamad Anda Falahuddin; Triaji Pangripto Pramudantoro (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2026)
The refrigeration industry continues to grow amid global challenges related to the environmental impact of refrigerant use. One of the commonly used refrigerants today is R-134a, but this refrigerant has a global warming potential (GWP) of 1430. As an alternative, R-600a is considered because it has a very low GWP of only 3, and has good compatibility with R-134a-based systems. This study aims to analyze the performance of the refrigeration system after retrofitting from R-134a to R-600a. Tests were conducted at two condensing temperature variations: 33.29°C and 35.29°C. The results show that at 33.29°C, COP increased by 30%, efficiency increased by 12%, and electricity consumption decreased by 32%. At 35.29°C, COP increased by 22%, efficiency by 6%, and electricity consumption decreased by 30%. In addition, R-600a requires only 50% of the refrigerant mass compared to R-134a. A temperature of 33.29°C was considered the optimal condition with the best performance and faster cooling time. These results support the potential of R-600a as an environmentally friendly alternative refrigerant.